THE PROTECTION OF CULTURAL HERITAGE AND THE ROLE OF CULTURE IN PROMOTING EUROPEAN INTEGRATION - Torta, Giula (2019)
This article analyzes the legal protection of cultural heritage, and the role of cultural heritage, in the promotion of integration into the European Union. Within the legal field, the notion culture derived from the preamble of the UNESCO Universal Declaration on Cultural Diversity is considered as a fundamental norm; which is contrasted from the perspective of International Law, and subsequently, under the legal framework of the European Union, in order to understand the role of culture in promoting integration within the European Union.